Organizational and managerial bases of activity of the Kharkiv Regional Sumo Federation - Байрамов, Руслан; Бондар, Анастасія (Slobozhanskyi Herald of Science and Sport, 2019)
Bairamov Ruslan & Anastasia Bondar Purpose: to characterize the organizational and managerial bases for the activity of the Kharkiv Regional Sumo Federation. Material & Methods: the study analyzed the Charter of the Kharkiv Regional Sumo Federation, training programs on sumo, to assess the activities of the Federation a survey was conducted among residents of the Kharkiv region, 230 people took part in it from 17 to 55 years, the sample type is random, the sample calculation was carried out according to the standard methodology, the SWOT analysis was used to assess the environment of the federation, 15 specialists from the sphere of physical culture and sports took part in it. Results: revealed that the public organization "Kharkiv Regional Sumo Federation" was registered in 2009 with the aim of promoting the development of sumo, acting on the basis of the Charter. In the Kharkiv region, 94 athletes are engaged in sumo, while 48.7% of the surveyed residents of the Kharkiv region consider sumo as an unpopular sport in our country, 76% of respondents are not interested in this sport at all, and only 4.3% are interested, while a low level of awareness has been revealed population of sumo in the region. 80% of respondents consider it necessary to develop sumo in the Kharkiv region. Conclusions: the results obtained complement and expand modern scientific data on the development of non-Olympic sports, sumo development, methods of teaching sumo. The study determined the state of development of sumo in the Kharkiv region, the structure, activities of the public organization of physical culture and sports direction "Kharkiv Regional Sumo Federation" in accordance with the Charter. Surveys of ordinary citizens showed that, in the opinion of most of them, the Federation should intensify marketing activities, increase the number of broadcasts of competitions on television, create official websites of federations and clubs on the Internet. Estimates of experts confirm the opinion of citizens, the greatest opportunities for the further development of the federation are opened by the popularization of sumo among the population and the expansion of the range of the federation itself, the improvement of quality and advertising of its services, as well as legislative changes. According to ordinary citizens and according to experts, the state should have the least impact on the development of sumo in our country and on the activities of the Federation.